2018
DOI: 10.1039/c7sc04430e
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and relative facial selectivities in organocatalytic asymmetric chlorocyclization reactions

Abstract: For four related 1,1-disubstituted olefins, (DHQD)2PHAL-catalyzed asymmetric chlorocyclization delivers Cl+ uniformly to one π face, but cyclizes with strong but differing net syn vs. anti addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 94 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…43,44 State-of-theart research, oen uses an integrated computational and experimental approach to gain such knowledge, as exemplied by the collaborative works of Jackson and Borhan. [37][38][39] On the computational side, static DFT calculations are routinely used, due to the availability of several user friendly soware, limited hardware requirements and the extensive development of this approach. [45][46][47] Most static DFT calculations simplify solvation effects by implicit solvation models, negating the possibility of observing explicit interactions between the solvent and reactants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 State-of-theart research, oen uses an integrated computational and experimental approach to gain such knowledge, as exemplied by the collaborative works of Jackson and Borhan. [37][38][39] On the computational side, static DFT calculations are routinely used, due to the availability of several user friendly soware, limited hardware requirements and the extensive development of this approach. [45][46][47] Most static DFT calculations simplify solvation effects by implicit solvation models, negating the possibility of observing explicit interactions between the solvent and reactants.…”
Section: Introductionmentioning
confidence: 99%
“…The foundation of this research is formed by other reports from both groups, investigating the reaction pathways of the non-catalysed halolactonization as well as other halocyclization reactions by means of a combination of experiments and static DFT calculations. 38 In 2016, they proposed a concerted nucleophile-assisted alkene activation (NAAA) mechanism for a non-catalysed halolactonization reaction, supported by kinetic isotope effects and the nucleophile proximity observed during NMR experiments and static DFT calculations ( Scheme 1b ). 39 Already more than 50 years ago, Shilov, among others, observed that the nucleophile could influence the rate and regioselectivity of electrophilic halogen additions, suggesting the classic mechanism was oversimplified in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the results from the structural analysis of the N–H catalysts (Figure ), we hypothesize the origin of enantiodivergence might come from a different binding model or sequence between catalyst and substrate or reagent (Br source), which could be strongly influenced by the presence of a free N–H amide. Indeed, recent studies by Borhan et al nicely demonstrated that fragment interaction among halogen source, catalyst, and olefinic acid is crucial for highly enantioselective chlorolactonization …”
Section: Resultsmentioning
confidence: 99%
“…This overgeneralized textbook scheme of stepwise mechanism was also widely used and invoked in many recent publications. , However, an alternative concerted addition mechanism was also provided to elucidate the observation that reaction rates were accelerated by proximity of the nucleophilic component to the alkene during the past few decades by many groups (Shilov and Staninets, Williams, Cambie, and others) . Very recently, Jackson, Borhan, and Denmark reaffirmed this concerted Ad E -3-type mechanism where electron donation from the nucleophilic addition partner activates the alkene for electrophilic attack, namely a nucleophile-assisted alkene activation (NAAA) process …”
Section: Introductionmentioning
confidence: 99%